The Impact of Digital Leadership on Organizational Innovation and Competitive Advantage: A Systematic Literature Review - Noah Alexander Gozali; Jonathan Hendraja; Nicolas Sunu; Dicky Larson; Sergio Bravo Arden (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
In the era of rapid digital transformation, the presence of digital leadership has become a key factor for organizations to maintain competitiveness. Digital leadership is understood as a leader’s ability to leverage digital technologies to drive changes in organizational attitudes, behaviors, and performance. This literature review aims to systematically examine the relationship between digital leadership, organizational innovation, and competitive advantage. The systematic literature review (SLR) method was conducted by identifying recent scholarly articles (2015–2025) related to this topic using leading academic databases. The review findings indicate that digital leadership contributes positively to organizational innovation by facilitating the adoption of new technologies, fostering an innovation-oriented culture, and empowering employees to engage in creative activities. Organizational innovation supported by digital leadership subsequently becomes a source of competitive advantage, as it enables product/service differentiation and improvements in operational efficiency. Several studies highlight that digital leadership strengthens competitive advantage both directly and through innovation ambidexterity. Other findings demonstrate indirect effects, for example through employee commitment and the organization’s digital culture. In conclusion, digital leadership plays a crucial role in driving innovation and organizational competitive advantage. This review suggests further quantitative research to test the proposed conceptual model, including mediating variables such as digital organizational culture or innovation capability.